Quality of Virgin Coconut Oil with Addition of Peppermint Oil - Clarissa Hanjaya; Fransiscus Sinung Pranata; Yuliana Reni Swasti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Virgin coconut oil (VCO) is a pure coconut oil made from mature and fresh coconut meat. VCO is consumed for health-related reasons, but the unsaturated fatty acids of VCO are prone to oxidation. Mixing VCO with peppermint oil, which contains antioxidants, inhibits the oxidation of unsaturated fatty acids and thus prevents the rancidity of VCO. This research used the antioxidants from peppermint oil to improve VCO quality. VCO contains antioxidants, such as α-pinene, menthol, 1,8-cineol, camphor, flavonoid, borneol, tocopherol, and carotene. The treatments consisted of three peppermint oil concentrations (2.5%, 5%, and 7.5%) in VCO. Results showed that the additionof peppermint oil significantly improved VCO quality. The optimal concentration of peppermint oil in VCO was 7.5% with a water content of 0.05%, a free fatty acid value of 0.13%, a peroxide value of 0.53 mg eq/kg, an iodine value of 4.42 g I2/100 g, a total plate count of 0 cfu/mL, and antioxidant activity of 90.28%.